Peculiarities of the eutrophication of the Amur Bay (Japan Sea) by Razdolnaya River - T. A. Mikhaylik; A. P. Nedashkovsky; N. D. Khodorenko; P. Ya. Tishchenko (Известия ТИНРО, 2020)
Data on dissolved organic concentration (DOC) and concentration of nutrients (phosphorus, silicon, and nitrogen of ammonium, nitrite and nitrate) in the Razdolnaya/Suifen River water are presented. The samples were collected fortnightly, as a rule, during more than a year (2013–2014). The nutrients concentration decreased and DOC and humic substances concentration increased with the river run-off increasing. In conditions of monsoon climate, the nutrients discharge from the Razdolnaya/Suifen into the Amur Bay had great pulsations that promoted sometimes producing of «excessive» phytoplankton biomass in the bay and provided a background for hypoxia at the bottom. Natural terrestrial fluxes of nutrients and DOC into the bay are much higher than these substances supply with waste waters of Vladivostok City. Interannual variability of the nutrients and dissolved organics fluxes into the Amur Bay is traced. Tendency to their increasing is supposed since 2003 because of the Razdolnaya/Suifen River annual discharge increasing observed by Hydrometeorological Agency in 2003–2017.